EKSISTENSI HUKUM WARIS ADAT DALAM SISTEM HUKUM DI INDONESIA - Ciendy, Erissa Maydina; Althaf, Rafikhansa (Gapenas Publisher, 2023)
This paper explains about the application of inheritance law in Indonesia and describe regarding customary law in the Indonesia legal system inconnection with Indonesia cionstitusian and other national law level and its impact toward the customary law application in the field. As well as exploring how the customary inheritance law system influences the field of customary law, especially in matters of inheritance. This analysis notes the significant role of the kinship system in shaping and influencing the provisions of Customary inheritance law in Indonesia, resulting in three main systems: patrilineal, matrilineal, and parental or bilateral. The implications of this existence can provide in-depth insight into the relationship between aspects of customary inheritance law and the legal system in Indonesia